The Potential of Mechanic Vibration for Generating Electric Energy - Hakim, Muhammad Afta Dzikril; Amiruddin, Muhammad; Hasto, Ken; Margono, Margono; Harjanto, Imadudin; Carsoni, Carsoni; Farikhah, Irna; Setyoadi, Yuris; Nuroso, Harto; Kaltsum, Ummi (Advance Sustainable Science, Engineering and Technology, 2020)
The purpose for this study is to convert mechanical vibration into electrical Power. Our target is to provide enough power for 1.2 V rechargeable battery having 160 . The investigation was conducted experimentally in electrical mechanical engineering laboratory. Four piezoelectric was connected to circuits in series mode called 1 module. In order to recharge the battery having voltage 1.2 volt, the measurement of the intensity of the loudspeaker was verified. According to table 1, it was found that at 2 Â of vibration is best because the value is 1.4 V nearest to 1.2 V. It was found that the mechanical vibration can be converted into electric power. It was found that to recharge 160 Â having 1.2 V, the 20 modules are needed.